2012
DOI: 10.1038/jp.2012.28
|View full text |Cite
|
Sign up to set email alerts
|

Proactive management of extreme prematurity: disagreement between obstetricians and neonatologists

Abstract: Objective: To verify, in extremely preterm infants, if disagreement between obstetricians and neonatologists regarding proactive management is associated with early death.Study Design: Prospective cohort of 484 infants with 23 0/7 to 26 6/7 weeks, without malformations, born from January 2006 to December 2009 in eight Brazilian hospitals. Pro-active management was defined as indication of X1 dose of antenatal steroid or cesarean section (obstetrician) and resuscitation at birth according to the international g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 29 publications
3
33
0
5
Order By: Relevance
“…Another study conducted in the United States found that among 271 premature infants with a gestational age of 23-30 weeks, birth weight of between 400 and 1000 g, and 5-min Apgar score of 0 or 1, 34% were alive at 18-22 months old [38]. This difference in preterm survival following birth asphyxia between Brazilian and American data is probably more related to the difficulties in the quality of hospital care than to the decision of obstetricians and pediatricians to invest in such care [9].…”
Section: Discussionmentioning
confidence: 70%
“…Another study conducted in the United States found that among 271 premature infants with a gestational age of 23-30 weeks, birth weight of between 400 and 1000 g, and 5-min Apgar score of 0 or 1, 34% were alive at 18-22 months old [38]. This difference in preterm survival following birth asphyxia between Brazilian and American data is probably more related to the difficulties in the quality of hospital care than to the decision of obstetricians and pediatricians to invest in such care [9].…”
Section: Discussionmentioning
confidence: 70%
“…During the past 5 years, large cohort studies from developed nations in North America, 1113,20,21 South America, 22 Europe, 14,15,2325 Asia, 18,19,26 and Australia 27 have reported estimates of gestational age-specific survival following periviable birth. Direct comparisons of estimated survival rates among these studies are limited, however, by potential biases introduced from differences in the data sources, ascertainment of death, selection of denominators, and definitions of live birth.…”
Section: Estimates Of Gestational-age Specific Survivalmentioning
confidence: 99%
“…Guinsburg et al considered that antenatal care was active when corticosteroids were administered or a caesarean delivery was performed 17. Serenius et al added to the definition of active care delivery in a level 3 maternity unit and tocolytic treatment 18.…”
Section: Discussionmentioning
confidence: 99%